FROM FLEXITIME TO FUTURETIME: A GLOBAL SYNTHESIS OF TIME-BASED FLEXIBILITY RESEARCH (2022–2024) - Mochamad Malik Akbar Rohandi; Alfira Sofia; Allya Roossalyn Assyofa (Jurnal Manajemen dan Bisnis Performa, 2026)
This study aims to systematically review the literature on time flexibility, flexible working, and flextime in the context of post-pandemic work. Using the PRISMA method, the study identifies trends, gaps, and key contributions from literature published between 2022 and 2024. The findings reveal a convergence of meaning among the concepts of time flexibility, flexible working, and flextime, highlighting the urgent need for an integrative temporal framework. This research contributes to theory by mapping the taxonomy of time flexibility and providing policy implications for the development of hybrid work models in the digital era. Time flexibility emerges as a critical factor in integrating productivity and well-being assessments within HR policies. It is essential that organizations adapt flexible policies to accommodate variations in employee age, gender, and family roles, ensuring inclusivity and effectiveness in the modern workforce. However, the study is limited to data collected from Scopus, which may not encompass all relevant perspectives. The insights from this study are valuable for shaping future research and offering practical guidance for organizations navigating the complexities of hybrid work environments in the post-pandemic era.